Comparative Analysis of Biomaterials and Biodevices Utilized in Cardiac Surgery: A Multinational Study - Grace Goldstein; Vaishnaw Rachel; Bulczynski Neeshi (Journal of Biomedical and Techno Nanomaterials, 2024)
Cardiac surgery is a critical field where the selection of biomaterials and biodevices can significantly impact patient outcomes. Different countries utilize various biomaterials and biodevices in cardiac procedures, influenced by factors such as technological advancement, regulatory environments, and healthcare infrastructure. Understanding the comparative effectiveness of these materials and devices across different regions is essential for optimizing patient care. This study aims to conduct a comparative analysis of biomaterials and biodevices used in cardiac surgery across multiple countries. The research seeks to evaluate the effectiveness, safety, and patient outcomes associated with these materials and devices, providing insights into best practices and potential areas for improvement. A mixed-methods approach was employed, combining quantitative data from clinical trials and patient records with qualitative insights from healthcare professionals. Data were collected from cardiac surgery centers in the United States, Germany, Japan, and Brazil. Quantitative measures included patient recovery rates, complication rates, and device longevity. Qualitative data were gathered through interviews and surveys with surgeons and medical staff, focusing on their experiences and perceptions of the materials and devices used. The study found significant variations in the effectiveness and safety of biomaterials and biodevices across different countries. Biomaterials used in Germany and Japan showed higher patient recovery rates and lower complication rates compared to those used in the United States and Brazil. Differences in regulatory standards, technological access, and surgeon preferences were identified as key factors influencing these outcomes. Qualitative data indicated a preference for locally produced devices in Japan and Germany, attributed to higher perceived quality and reliability. This multinational study highlights the disparities in the use and outcomes of biomaterials and biodevices in cardiac surgery. The findings suggest that adopting best practices and high-quality materials from countries with superior outcomes could enhance patient care globally. Further research and international collaboration are recommended to standardize the use of biomaterials and biodevices, ensuring optimal patient outcomes in cardiac surgery.